1999
DOI: 10.1177/19714009990120s226
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Chiari Malformation: A Morphometric Study of the Posterior Cranial Fossa

Abstract: To investigate overcrowding in the posterior cranial fossa as the pathogenesis of adult type Chiari malformation, we morphometrically studied the brainstem and cerebellum within the posterior cranial fossa as well as the occipital bone while taking into consideration their embryological development. Compared with the control group, the Chiari group had a significantly larger “volume ratio” as PFBV/PFCV, the three occipital enchondral parts (the basiocciput, exocciput and supraocciput) were significantly smalle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
185
5
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(206 citation statements)
references
References 3 publications
13
185
5
3
Order By: Relevance
“…Most CM-I patients involve syringomyelia, which is an abnormal dilatation of spinal canal creating a small cavity that can involve a collection of cerebrospinal fluid (CSF) [5]. CM-I may arise from several reasons, including altered CSF circulation dynamics that disrupt the equilibrium of intracranial pressure [2], incomplete development of occipital bones and small posterior cranial fossa (PCF) that results in an overcrowding of cerebellum [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Most CM-I patients involve syringomyelia, which is an abnormal dilatation of spinal canal creating a small cavity that can involve a collection of cerebrospinal fluid (CSF) [5]. CM-I may arise from several reasons, including altered CSF circulation dynamics that disrupt the equilibrium of intracranial pressure [2], incomplete development of occipital bones and small posterior cranial fossa (PCF) that results in an overcrowding of cerebellum [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In Chiari anomaly type II, herniation of the cerebellar vermis (paleocerebellum) is found with caudal dislocation of the lower brain stem, occasionally dorsal deformation (protrusion) of the medulla oblongata, lateroanterior development of the cerebellar hemispheres (reverse cerebellum), and ascending course of the cervical nerve roots, usually without histological dysgenesis in any parts of the brain except for insignificant heterotopia, (A complication of the type II anomaly in 57.1% of fetal spinal dysraphism [1] or that of spinal dysraphism in 53.8% of the fetal Chiari type II anomaly [personal data] is well known.) This explanation is further supported by the observations of Stovner et al [9], who found a relationship between the intensity of cerebellar herniation and hypoplasia of the posterior fossa, and of Nishikawa et al [7], who explored the overcrowding of the posterior fossa with normal volume of the infratentorial structures, especially in Chiari type I and/or adult Chiari anomalies. It should be noted that Chiari [2] described the hypoplasia of the basicra-462 nium ("shortened clivus") in "type II" in his original report in 1891.…”
Section: Treatment Of the Chiari Malformation By Drs He James And mentioning
confidence: 83%
“…He later noticed that the severity of the hydrocephalus did not relate to the extent of the malformation and postulated that the defective growth of the skull caused increased local pressure, presumably forcing the descent of the hindbrain [12]. Modern morphometric neuroimaging studies have compared patients with CMI with healthy subjects to measure the skull base and overcrowding of the posterior cranial fossa structure [31][32][33]. These comparisons support that an underdeveloped occipital bone is the main abnormality in CMI, with a normal posterior fossa brain volume similar to that found in healthy subjects.…”
Section: Pathogenesis Of Chiari I Malformation and Headachesmentioning
confidence: 98%
“…Experimental models have shown that this malformation results from the underdevelopment of the occipital somite that embryologically originates from a primary paraxial mesoderm insufficiency. This occurs after closure of the brain-forming neural folds takes place, thereby inducing an overcrowding of the posterior fossa [33].…”
Section: Pathogenesis Of Chiari I Malformation and Headachesmentioning
confidence: 99%